Collaboration in mitigating spatial and skills mismatch: Exploring shared understandings between transit planners and workforce professionals - Andrew Guthrie; Fernando Burga; Yingling Fan (Journal of Transport and Land Use)
Transit-dependent workers frequently find themselves caught between spatial mismatch (a lack of transportation options to reach jobs one is qualified for) and skills mismatch (a lack of needed qualifications for jobs one can reach). Historically, policy responses to these twin problems have essentially been siloed, with some responses focused on improving disadvantaged workers’ mobility and others on skills training. Using the Twin Cities as an example of a healthy regional economy with areas of persistent disadvantage, this paper addresses the following research question: How do transit planners and workforce development professionals perceive the issues of spatial and skills mismatch and collaboration? This analysis explores this question through in-depth interviews with 16 transit planners and workforce development providers involved with one or more of seven study areas. The authors create an explanatory typology of areas to address with integrated transit planning and workforce development, interpret informants’ intersubjective understandings of the state of efforts, and apply Innes and Booher’s Diversity-Interdependence-Authentic Dialogue (DIAD) model of collaborative rationality to explore opportunities for deepening collaboration. The paper concludes with policy recommendations to connect marginalized workers with broader opportunities through transit planning and workforce development collaboration.